Experimental analysis of photovoltaic thermal collector (PVT) with nano PCM and micro-fins tube counterclockwise twisted tape nanofluid - Bassam, Abdulsahib M.; Sopian, Kamaruzzaman; Ibrahim, Adnan; Al-Aasam, Anwer B.; Dayer, Mojtaba (Case studies in thermal engineering, 2023)
A hybrid PVT (photovoltaic thermal system) nanofluid circulation system was tested, which included a micro-fin tube (inner grooved) and twisted tape with nano PCM (phase change material). The use of nanoparticles allowed the nano PCM and nanofluid to have higher thermal conductivities, improving their performance. Experiments were carried out within a controlled environment by utilizing an indoor solar simulator with a solar irradiance level of 800W/m2. The PVT system used water/SiC (0.6, 0.3) vol% nanofluid as a working fluid. The nanoPCM comprises 1% SiC nanoparticles, which enhance thermal, electrical (photovoltaic), and photovoltaic thermal efficiency (total efficiency). The mass flow rate range is 0.008–0.058 kg/s. The energy analysis showed that the PVT had an electrical efficiency of 10.8%. The system's maximum thermal efficacy was 83.3% for the PVT with the T (twisted tape), MF (micro-fins), NF (nanofluids), and NPCM (Nano PCM). The percentage of improved electrical power compared between the bare PV and the PVT NF T NF NPCM was 44.5%. The micro fin tube with twisted tape improved the heat transfer properties for enhanced thermal performance.